A study on the reading interests of the second year, third year and fourth year students in Parada High School - Manansala, Bianca Camille A.; Dela Torre, Nathalie N. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
This study is about the reading interests of the second year, third year students in Parada High School. It aims to find out if there are significant relationship between the reading interests of the students and their academic performance as represented by their class section. It also analyzes if there are significant relationship between students' reading interest on a particular material and frequency of days spent on reading them in the library. Moreover, the frequency of library use, and the length of time spent in the library by the students are also the focus of the study.
The data gathered was tabulated and subjected to chi-square test to know if there are relationships between the variables and it was found out that the reading interest of fourth year respondents regarding the titles of magazines read has a significant relationship with academic performance represented by class sections. Furthermore, the computed value of chi-square among the second year, third year and fourth year levels regarding the relationship between reading interest on a particular material and the frequency of days spent on reading the materials in the library are proven to have significant relationships. Therefore, student' reading interest on different reading materials are defined by how much time they spend on reading them.
After the findings have been revealed, the researcher recommends that the library orientation must be given to the students at the start of the school year for them to be informed on the various materials that may be found in the library; librarians should play an active role in supporting and providing the information needs of the students by ensuring that students gather the right information and materials; teachers and school administrators must collaborate with the school librarian in promoting to the students the importance of the library in their learning process; teachers must include on their lesson plans activities that need the use of library materials; and to enhance the interests in reading among students, they should be exposed to different activities and programs that deal with extensive reading.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Reading interests -- Philippines -- Bulacan (Sta Maria).; High school students -- Books and reading